Planos municipais de gestão integrada de resíduos sólidos : desafios na implementação da política nacional de resíduos sólidos na bacia hidrográfica Tietê Jacaré – SP - Santiago, Cristine Diniz (2016)
In Brazil, waste management has developed with delay when compared to some countries which sought solutions for the area in advance. The national legislative framework is the National Waste Policy (NWP), Law n. 12.305/2010, regulated by Decret n. 7.404/2010, which decentralizes waste management, according to the pattern established on the National Environment Policy. Decentralization is explicited by the proposition of a tool called Integrated Waste Management City Plan (IWMCP), which has proved to be a challenge to municipalities. This research analyses the elaboration process of IWMCPs – five years after the passing of the NWP – in municipalities of the 13 th Hydric Resources Management Unit (HRMU) in São Paulo state – Tietê Jacaré’s HRMU, through surveys and multiple case studies. Results show the complexity and uniquenesses of the cities, highlighting the absence of data, resources and technical staff capacitation as main barriers, and the possibility of hiring companies to elaborate the IWMCP as the main facilitator according to the cities. Other incipient aspects present in the city planning process are the search of joint solutions and social participation. Thus, the decentralization proposed by the NWP presents difficulties for the law enforcement since municipalities still do not rely on the necessary means to develop complex planning as recommended by the NWP. This way, efforts from both the federal and state governments are recommendable aiming at the capacitation and resources availability, what shall make the city emancipation possible throughout the planning process. The proposal of alternatives for shared solutions is also crucial for the waste management optimization, as prioritized by the NWP.